Avaliação in vitro e in vivo da toxicidade do composto 2,2 -disseleneto de ditienila em ratos - Chagas, Pietro Maria (2013)
The compound 2,2 -dithienyl diselenide (DTDS), an organoselenium compound with thiophene moieties, has been proven to be a promising antioxidant in vitro and in vivo, as well as an antifungal and antimicrobial agent. However, its toxicity, an important point to be investigated, has not been evaluated. The objective of this study was to evaluate whether DTDS has potential toxicity in vitro or in vivo. For this reason, sulfhydryl enzyme activities, such as δ-aminolevulinic acid dehydratase (δ-ALA-D) and Na+, K+-ATPase were assessed to predict in vitro DTDS toxicity in rat brain homogenate, in addition to its thiol oxidase-like activity. In other section of experiments, DTDS was administered to rats (50 or 100 mg/kg; per orally) in order to determine toxicological parameters in vivo. Plasma samples were collected in order to measure the biochemical parameters: alanine (ALT) and aspartate (AST) aminotransferase activities and urea and creatinine levels. Besides, in brain homogenates, it was determined the activity of the enzymes δ-ALA-D and Na+, K+-ATPase, as well as lipid peroxidation levels and antioxidant defenses (catalase and superoxide dismutase activities and ascorbic acid and reduced glutathione levels). The compound DTDS inhibited in vitro both δ-ALA-D and Na+, K+-ATPase activities (IC50 2 μM and 17 μM, respectively). The DTDS inhibitory effect on δ-ALA-D and Na+, K+-ATPase activities was restored by dithiol dithiothreitol. In addition, DTDS (5-25 μM) showed a thiol oxidase-like activity. In vivo, DTDS (50 and 100 mg/kg) caused a decrease in food and water intakes and the loss of body weight, indicating systemic toxicity, even causing death of the animals. At a dose of 100 mg/kg, DTDS decreased urea levels and increased plasma alanine and aspartate aminotransferase activities. Lipid peroxidation was increased in both administered doses. Moreover, in the highest dose, DTDS inhibited δ-ALA-D activity. By contrast, neither Na+, K+-ATPase activity nor antioxidant defenses were altered in the brain of rats exposed to DTDS. In conclusion, the interaction with thiol groups of sulfhydryl enzymes seems to mediate the inhibitory effect of DTDS against δ-ALA-D and Na+, K+-ATPase activities in vitro. Furthermore, in the administered doses, DTDS causes cerebral and systemic toxicity in rats. Although other studies are necessary to give more information about this specific compound, our findings contribute to the knowledge on the toxicology of DTDS, a compound with pharmacological properties.